MOVING TOWARDS EVIDENCE BASED NURSING PRACTICE IN PAKISTAN - Muhammad, Dildar (Annals of Allied Health Sciences, 2017)
Around the globe, there is a growing emphasis on evidence-based practice for improved pat ient outcomes. Developed countries have succeeded in achieving the high level of patient care. However, developing countries are lagging behind in providing optimum care to patients’ families and communities. Pakistan, as a country, has overall poor health indicators and the quality of healthcare at primary, secondary and tertiary level is generally not appreciable. The role of nursing in reducing morbidity, mortality and improving the healt h status of individuals and communities in undeniable. Globally, nurses have played an active role in providing quality nursing care to pat ients. From t radit ional, route practice the nursing care has, nowadays, become a more refined and sophist icated based on evidence. Nevertheless, in Pakistan, the nursing fraternity has still to realise the importance of evidence-based practice. To move towards evidence based nursing practice, the nursing profession has to make a long journey. Fostering a research culture in nursing community is one of the utmost challenges. The status of nursing research in the country is not at par with international standards. Conducting quality research studies having practical implications for patients, their families and communities is the need of the hour. Graduate education is the key to move towards the goal of evidence based nursing practice. There is a dearth of graduate nursing programmes offered by Pakistani universities and only few Universit ies are offer ing MScN programmes. To improve the quality of nursing care in hospitals in Pakistan, there is a need to educate nurses to graduate level who can become researchers and scholars having the potential to conduct quality research studies focusing indigenous issues. Such inquiries may also promote culturally sensitive care to patients, families and communities. There is also a need for nurse scholars, academics and researchers to gather on a platform and design a national strategy to foster a culture of evidence based practice. Areas of high priority to for nursing research may be identified as per the need of the country. Collaboration among nurse academicians is needed for promoting a culture of nurturing and professional growth. It is pertinent to mention here that though there are many nursing journals published around the world, in Pakistan there is no journal specifically focused on nursing and midwifery. Once the scholarly activity is initiated, journals specifically focused on nursing issues may be established. To improve patient outcomes evidence based nursing practice is needed in Pakistan. Graduate education of nurses is the first step to move towards EBP. Collaboration among nurse academics and practitioners as well as with other healt h professionals is another suggested measure to build a culture of evidence based practice.